2009
DOI: 10.1021/ef800342r
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Combustion and Emission Characteristics of a Diesel Engine with Oxygenated Fuels and Thermal Barrier Coating

Abstract: The purpose of the present study is to investigate the influence of fuel additives [2-methoxyethyl acetate (MEA)] plus thermal barrier coating (TBC) on diesel engine performance, combustion, and emission characteristics. A plasma spray coating (PSC) technique was used to coat the cylinder head, valves, and piston crown with ZrO 2 /Al 2 O 3 of about 150:150 µm. The additives are in the ratio between 0.5 and 2.0%, with 0.5% intervals. They were added to neat diesel fuel, by volume, respectively. In general, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Gong et al 2 found that diesel engine fueled with 2-methoxyethyl acetate can reduce smoke, HC, CO, and NOx emissions. Ramu et al 3 have studied the influence of fuel additives (2-methoxyethyl acetate) plus thermal barrier coating (TBC) on diesel engine performance, combustion, and emission characteristics. Their results showed that NOx emission was further reduced by 10 % in the fuel additive plus thermal-barrier-coated engine.…”
Section: Introductionmentioning
confidence: 99%
“…Gong et al 2 found that diesel engine fueled with 2-methoxyethyl acetate can reduce smoke, HC, CO, and NOx emissions. Ramu et al 3 have studied the influence of fuel additives (2-methoxyethyl acetate) plus thermal barrier coating (TBC) on diesel engine performance, combustion, and emission characteristics. Their results showed that NOx emission was further reduced by 10 % in the fuel additive plus thermal-barrier-coated engine.…”
Section: Introductionmentioning
confidence: 99%
“…This material has been widely studied because of its unique properties such as hardness, chemical stability, refraction, and ionic conductivity . These distinctive properties make zirconia a good choice for a wide range of applications, such as solid fuel cells, ceramics, thermal barrier coating materials, catalysts, pigments, and luminescent materials or sensors when doped by rare earth elements. These applications depend not only on the structural properties and crystallinity, particle size, and morphologies of zirconia but also on its porosity . Zirconia has been synthesized by various methods such as sol–gel process, coprecipitation , hydrothermal or solvothermal synthesis, pulsed plasma technique, aerosol pyrolysis, , and more recently, sustainable methods such as gelation of alginate, precipitation by hydroxypropyl-β-cyclodextrin, use of lysozyme, which is a cationic antibacterial enzyme, and use of Fusarium oxysporum , which is a species of plant parasitic fungus .…”
Section: Introductionmentioning
confidence: 99%
“…Zirconia nanoparticles (NPs) exhibit several interesting properties,13 which results in them being useful in many fields of technology such as solid fuel cells,4 ceramics,5 thermal barrier coating materials,6 catalysts,7,8 and pigments 9. Several methods have been developed to synthesize zirconia nanoparticles, which include the sol–gel process,10 precipitation,11 hydrothermal,12 and pulsed plasma technique 13.…”
Section: Introductionmentioning
confidence: 99%